2022
DOI: 10.1242/dev.200683
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of the maternal membrane oestrogen receptor ERα alters expansion of trophoblast cells and impacts mouse fertility

Abstract: The binding of 17β-oestradiol to oestrogen receptor alpha (ERα) plays a crucial role in the control of reproduction, acting through both nuclear and membrane-initiated signalling. To study the physiological role of membrane ERα in the reproductive system, we used the C451A-ERα mouse model with selective loss of function of membrane ERα. Despite C451A-ERα mice being described as sterile, daily weighing and ultrasound imaging revealed that homozygous females do become pregnant, allowing the investigation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…However, it is also possible that E 4 impairs embryonic development as the absence of membrane signaling of ERα was recently shown to interfere with placentation leading to infertility (39).…”
Section: Chronic E 4 Treatment Decreases the Number Of Oocytes Ovulat...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also possible that E 4 impairs embryonic development as the absence of membrane signaling of ERα was recently shown to interfere with placentation leading to infertility (39).…”
Section: Chronic E 4 Treatment Decreases the Number Of Oocytes Ovulat...mentioning
confidence: 99%
“…Although this infertility largely relies on placental defects during development (39), this model offers the opportunity to assess the role of membrane-initiated action of ERα on the positive feedback of estrogens. Second, estetrol (E 4 ) is an estrogen exclusively synthesized in human fetal liver which selectively binds ERs (ERα and ERβ) but with a lower affinity than E 2 (40).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation leads to female infertility [ 73 , 74 ]. Detailed reproduction phenotyping revealed that the C451A ERα mutant female mice can be pregnant but show a series of reproduction-associated abnormalities such as embryonic/neonatal death, delayed parturition, and small litter size [ 89 ]. This study showed abnormal placental development including altered behavior of a trophoblast cell population, which supports placentation and nourishes embryos.…”
Section: Erα Isoform Variation and Functionsmentioning
confidence: 99%
“…Taken together, these observations indicate that membrane-bound ERα by palmitoylation on C451 is important to support female reproduction, from an endocrine mechanism and placenta development. Although membrane-initiated ERα signaling is involved in estrogen-mediated energy homeostasis [ 90 , 91 , 92 ], C451A ERα mutant mice do not show body weight phenotype and abnormal fat accumulation [ 74 , 75 , 89 ]. E 2 prevents bone demineralization, which is significantly impaired in the mutant mice, indicating that this effect is primarily exerted by membrane-bound ERα [ 75 ].…”
Section: Erα Isoform Variation and Functionsmentioning
confidence: 99%